Chromatographic NMR spectroscopy: the effect of hollow silica microspheres on magnetic field inhomogeneities and resonance lineshapes. Issue 37 (17th September 2020) - De Biasi, Federico; Moro, Federico; Frezzato, Diego; Rastrelli, Federico
Abstract : We provide a description of the line broadening phenomenon observed in chromatographic NMR spectra with hollow silica microspheres. Abstract : Micrometric hollow silica spheres can effectively reduce magnetic field inhomogeneities when employed as a stationary phase in the context of NMR chromatography. We here provide a description of the NMR line broadening phenomenon for physically representative collections of hollow spheres with different geometries and filling factors. Our results highlight how, within the explored conditions, a proper modelling of the line broadening phenomenon should consider the enhanced relaxation of the spins during their diffusion across the spherical shells, and possibly other slow motional effects.